Enhancing Character Depth through Personality Exceptions for Narrative Planners - Rubin-McGregor, Elinor; Harrison, Brent; Siler, Cory (Proceedings of the AAAI Conference on Artificial Intelligence and Interactive Digital Entertainment, 2023)
In the field of narrative planning, implementing character personality is a challenge that’s been tackled many different ways. Most of these methods do not incorporate any method for personality to shift when characters are put in situations that would, through stress or satisfaction, naturally cause the character to behave differently than usual. Through use of situationally-triggered Personality Exceptions, we can support the generation of a story that prominently features such personality shifts as a narrative tool. This feature is made as generic as possible so that it can be attached onto a wide range of personality models in narrative generators. Through adapting Indexter’s indexes of narrative salience towards tracking internal narrative salience in the characters’ memories, we can accurately pinpoint triggers which are used to activate these personality exceptions in thematically relevant situations.